Analysis of intermittent training and small-sided games training methods and their impact on explosive power of the lower limbs in U19 soccer players. - Oussama, Messai; Sabira, Ferahtia; Toumi , Mebarka Sonia (Journal of Sport Science Technology and Physical Activities, 2026)
The study aims to identify the effectiveness of a proposed training program using two methods: Intermittent training and small-sided games training on developing explosive power in soccer players under 19 years old. For this purpose, we used the experimental method on a sample consisting of 10 players as an experimental sample and 10 players as a control sample, who we deliberately selected to collect data we used the Sargent high jump test. After collecting the results and processing them statistically using the SPSS statistical package, it was found that there were statistically significant differences in favor of the experimental group, and thus the effectiveness of the applied training program. On this basis, the study recommended combining the methods of intermittent training and small-sided games training to develop explosive power of the lower limbs.